Chitosan-gum arabic embedded alizarin nanocarriers inhibit biofilm formation of multispecies microorganisms. (15th May 2022) - Raj, Vinit; Kim, Yeseul; Kim, Yong-Guy; Lee, Jin-Hyung; Lee, Jintae
Abstract: Biofilm formation by microorganisms is a serious clinical problem that leads to drug failure. Nanocarriers (NCs) have shown good potential for controlling drug-resistant biofilms, although the effective penetration and retention of NCs in biofilms is still a big task. The issue was overcome by selecting alizarin as a natural antibiofilm agent, but its low water solubility restricts its further use. Thus, in present study, chitosan-gum arabic-coated liposomes-alizarin nanocarriers (CGL-Alz NCs) were synthesized using an ionotropic gelation method to improve drug release and penetration of alizarin inside biofilm cells. CGL-Alz NCs acted against biofilms caused by Candida albicans or Staphylococcus aureus and improved penetration of alizarin inside biofilms exerting long-term antibiofilm effects caused by sustained release of alizarin from NCs. Furthermore, significant biofilm and hyphae reduction was observed at a 5 μg/mL concentration of NCs. This research work opens a new avenue of an innovative strategy to treat biofilm-associated multispecies infections. Graphical abstract: Unlabelled Image Highlights: Chitosan formed nanocarriers via ionic gelation with negative charged gum arabic. Chitosan-gum arabic nanocarriers encapsulated the alizarin anchored liposomes. An improved kinetic release mechanism of alizarin nanocarriers was found. Nanocarriers exhibited antibiofilm activity against C. albicans and S. aureus .